STRATEGY FOR IMPLEMENTING KNOWLEDGE MANAGEMENT AT DINAS PERTANIAN DAN KETAHANAN PANGAN KABUPATEN BARRU - Lukman, Kurniyati; Lukman, Risnawati (Jurnal Administrasi Negara, 2024)
The implementation of knowledge management based on the Regulation of the Minister of State for Empowerment of State Apparatus and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2011 concerning Guidelines for the Implementation of Knowledge Management Programs at the Regional Government Level of Barru Regency has not demonstrated the implementation of directed and planned knowledge management. One of them is Dinas Pertanian dan Ketahanan Pangan, which provides an illustration that the implementation of knowledge management has not been running optimally. Based on these problems, this research aims to analyze the strategy for implementing knowledge management at Dinas Pertanian dan Ketahanan Pangan based on the concept of the strategy for implementing knowledge management, namely creating knowledge, storing knowledge, sharing knowledge, and utilizing knowledge. The research procedure used was descriptive-qualitative research and data collection methods through interviews, observation, and documentation review involving 11 informants. The results of the research show that various strategies have been implemented in implementing knowledge management at Dinas Pertanian dan Ketahanan Pangan. The first strategy is knowledge creation in the form of classical and non-classical education and training, knowledge storage strategies through the use of technology, and document archiving. Furthermore, sharing knowledge with the availability of employee chat rooms and meeting/discussion activities has been carried out regularly. There is another strategy, namely utilizing knowledge, which is demonstrated by the preparation of work guides and guidelines such as Standard Operating Procedures (SOP), but further development through the design of a knowledge management system has not been implemented.